Interdependence between the information evaluator and the decision maker* - HILTON, RONALD W. (Contemporary Accounting Research, 1986)
Abstract. A game theoretic model of the relationship between an information evaluator and a decision maker is formulated, and interdependence analysis is employed to decompose the game into several components. Each of these components represents one aspect of the interdependence relationship experienced by the information evaluator and decision maker. The analysis is then employed to distinguish among game forms. Résumé. Un modèle de la théorie des jeux établissant une relation entre un évaluateur d'informations et un décideur est proposé, et l'analyse d'interdépendance est utilisée afin de décomposer le jeu en plusieurs parties. Chacune de ces composantes représente une facette de la relation d'interdépendance vécue par l‘évaluateur d'informations et le décideur. Par la suite, l'analyse sert à établir une distinction parmi les “formes de jeu”.